Characterisation and properties of Oil Palm Fruit Bunch (OPFB)/ Polypropylene (PP) composites, PP Nanoclay/PP and OPFB/PP Nanoclay/PP Hybrid Composites / Anizah Kalam - Kalam, Anizah (2010)
In this study the oil palm fruit bunch fibres were used as the filler or reinforcement in polypropylene. Thus the aim of this thesis was to achieve a greater understanding of the various parameters that contribute to the variations of water absorption, thermal stability and mechanical properties, and to manipulate these parameters in order to produce an improved oil palm fruit bunch fibre reinforced polypropylene composite material. Several characterization techniques, such as tensile test, flexural test, impact test, water absorption analysis, thermal analysis and chemical analysis were used to assess the effect of each parameter. OPFB/PP composites at four different sizes of 250 |im, 180 |im, 125 urn and 100 |im were investigated on the water uptake ability and were found to increase as the OPFB size increase. Meanwhile the thermal stability decrease at temperature range of 200°C - 450 °C. The investigations also showed that the tensile and flexural properties were increased with the increasing of OPFB size and indicated that the 250 ^tm OPFB/PP composites had the most enhances mechanical properties. PPnanoclay/PP composites were compounded at four PPnanoclay loadings of 10 phr, 25 phr, 40 phr and 100 phr. The water uptake of PP nanoclay/PP composites was found to increase as the PPnanoclay loading increase followed by the increase in thermal stability as well.